Extracellular vesicles: key mediators in in vitro embryo production - Pournourali, Mostafa; Mizban, Nahid; Ehsani, Roxana; Ebrahimian, Somayeh; Nadri, Touba; Azari-Dolatabad, Nima (Frontiers in Veterinary Science, 2025)
Nano-sized extracellular vesicles (EVs) possess a lipid bilayer and are secreted from cells into their surrounding environment. The transport of multiple biomolecules, including DNA together with RNA, microRNAs (miRNAs), lipids, proteins, and metabolites, happens through biofluids via EVs for intercellular communication. Extracellular vesicles play crucial roles during the in vitro embryo production (IVEP) process. Specifically, the maturing oocyte benefits from EVs that facilitate cell-to-cell communication and transfer important biomolecules, which improve oocyte development potential. Moreover, EVs help establish important molecular control needed for oocytes to advance into the metaphase II phase, which enables proper fertilization events. In fact, the fertilization process depends heavily on EVs because seminal plasma-derived EVs play an essential role during fertilization, and they improve sperm motility as well as capacitation and the acrosome reaction, which are required for successful fertilization. EVs transport proteins together with RNAs, which enhance sperm capacity to fertilize. Embryos benefit from the optimal growth environment, which is maintained by oviduct and uterus-derived extracellular vesicles (EVs), as they support proper gene expression regulation. EVs produced in the oviduct enable embryo development, and those released by the uterus serve as communication channels for embryo-maternal environment integration required during implantation. These vesicles contain bioactive molecules such as miR-21, miR-26a, and HSP70, which are involved in key reproductive functions including granulosa cell (GC) signaling, oocyte maturation, and sperm function regulation. Overall, the reproductive system relies heavily on EVs because these vesicles manage oocyte development as well as the process of fertilization and embryonic development. The communication features of EVs using regulatory molecules indicate their potential role in assisted reproductive technologies (ARTs). Advancing our knowledge regarding EVs' mechanisms will support the development of novel strategies to enhance IVEP outcomes. This review provides an overview of the current understanding of the roles of EVs in oocyte maturation, fertilization, and embryo development.